PERUBAHAN KONSEPTUAL UNSUR PEMERASAN DALAM PARADIGMA KEJAHATAN SIBER - Hummerson, Andi Widiatno (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The rapid development of information and communication technology has transformed conventional crimes into increasingly sophisticated cyber-based offenses, particularly cyber extortion. In Indonesia, cyber extortion is primarily regulated under Article 27 paragraph (4) of Law No. 11 of 2008 on Electronic Information and Transactions (ITE Law), as amended by Law No. 1 of 2024, alongside extortion provisions in the Criminal Code (KUHP), namely Article 368 of the old KUHP and Article 482 of the New KUHP. This shift reflects a fundamental conceptual change in the elements of extortion, where coercion is no longer limited to physical violence but extends to digital threats, such as messaging-based intimidation and sextortion through social media platforms. This study aims to examine the regulation of cyber extortion under the ITE Law and to analyze its relationship with extortion provisions in the KUHP and the New KUHP. This research employs a normative juridical method with a conceptual and statutory approach, relying on primary legal materials in the form of legislation and secondary materials such as legal literature and scholarly works. The analysis is conducted deductively to interpret the elements of cyber extortion and the application of the lex specialis derogat legi generali principle. The findings indicate that the reformulation of Article 27 paragraph (4) into Article 27B paragraph (2) of the amended ITE Law was intended to clarify legal ambiguities and distinguish cyber extortion from cyber bullying. However, the removal of certain elements and shifts in the formulation of the offense have generated new interpretative challenges and normative overlap. Furthermore, while the ITE Law should function as lex specialis for digital-based extortion, judicial practice frequently applies it cumulatively with KUHP provisions to strengthen evidentiary requirements. This study concludes that a harmonized and hybrid approach is necessary to ensure legal certainty, proportionality of sanctions, and effective enforcement in the evolving ecosystem of cybercrime.